QUALITATIVE AND QUANTITATIVE PHYTOCHEMICAL ANALYSIS AND ANTIOXIDANT ACTIVITIES OF ARECA CATECHU NUT HUSK - Asiah Abdullah; Nurul Akmalina Sapaat; Sheikh Ahmad Izaddin Sheikh Mohd Ghazali; Nurazira Mohd Nor (Journal of Academia, 2022)
Areca cathechu nut also locally known as ‘pinang’ contains countless nutritional and functional components with different bioactivities. The areca nut is covered by fruit shell of husk that contains a lot of fibre. However, its husk was often thrown away and discarded as a waste. Thus, this study attempts to analyze antioxidant capacity of areca nut husk. The areca nut husk was extracted using three types of solvent of different polarity including n-hexane, ethyl acetate and ethanol. Qualitative phytochemical screening was carried out to determine the phytochemical constituents present in the extracts. The antioxidant capacity of areca nut husk was then evaluated quantitatively by determining total phenolic content and DPPH assay, respectively. Ethanolic extract revealed the presence of alkaloid, steroids, terpenoids, tannins, saponins, glycoside, flavonoid and phenol. Folin-Ciocalteu method was used to quantify the total phenolic content in the extracts using a calibration curve of gallic acid. Total phenolic content of ethanolic extract (558.33 mg GAE/g) was found higher than that of ethyl acetate and n-hexane extracts which were 436.48 mg GAE/g and 290 mg GAE/g, respectively. The ethanolic extract exhibited higher DPPH radical scavenging activity compared to ethyl acetate and n-hexane extracts with 72.14% ± 0.17 percentage of inhibition and IC50 value of 118.33 ± 0.51. The results obtained from this study revealed the potential of this underutilized areca nut husk as promising natural antioxidant.